Psalms 1 - 2 gateway to the Psalter - Cole, Robert Luther 1953- (Sheffield Sheffield Phoenix Press, 2013)
Literaturverz. S. [165] - 171
Includes bibliographical references (p. [165]-171) and indexes
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Commentaries; Kommentar